2005
DOI: 10.1002/ardp.200400927
|View full text |Cite
|
Sign up to set email alerts
|

New Oxadiazole Derivatives Showing partly Antiplatelet, Antithrombotic and Serotonin Antagonistic Properties

Abstract: Ten new 1, 2, 4-oxadiazole- and six new 1, 3, 4-oxadiazole-carboxamides containing different lipophilic moieties (i.e. 4-biphenyl-, 1-naphthyl, phenylpropyl- and n-hexyl substituents) and additional basic groups which are mainly alkyl- and dialkylaminoalkyl residues have been synthesized and tested for antiplatelet effects in vitro (Born-test) and antithrombotic properties in vivo (laser thrombosis model). If the platelet aggregation was induced by collagen, the inhibitory effects (IC50) were between 58 microM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 21 publications
(24 reference statements)
0
28
0
Order By: Relevance
“…As starting material we prepared 2-phenyl-2,3-dihydronaphto[1´,2´:4,5]furo [2,3-e] [1,2,4] triazine-3-on 1, using the straightforward synthesis described before. 6 Using this compound, all cleavage reactions with oxygen, sulfur or nitrogen nucleophiles are very easy and lead to good yields of the end products.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As starting material we prepared 2-phenyl-2,3-dihydronaphto[1´,2´:4,5]furo [2,3-e] [1,2,4] triazine-3-on 1, using the straightforward synthesis described before. 6 Using this compound, all cleavage reactions with oxygen, sulfur or nitrogen nucleophiles are very easy and lead to good yields of the end products.…”
Section: Resultsmentioning
confidence: 99%
“…6 Using this compound, all cleavage reactions with oxygen, sulfur or nitrogen nucleophiles are very easy and lead to good yields of the end products. 3a R 1 = R 2 = H 3b R 1 = H; R 2 = CH 3 3c R 1 = H; R 2 = phenyl 3d R 1 = H; R 2 = cyclohexyl 3e R 1 = H; R 2 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a number of previous publications, we were able to show that the substitution of heterocycles rich in nitrogen like purines [1], indazoles [2], triazoles [3], oxadiazoles [4], imidazoles [5], pyrimidocinnolines [6], phthalazines [7], or thiazoles [8] with a carboxamide partial structure in addition to basic groups leads to a wide variety of compounds with antiplatelet activities in micromolar concentrations. In this paper, we wish to report a number of pyrazole derivatives fulfilling these structural requirements and, consequently, were promising to show remarkable antiplatelet activities.…”
Section: Introductionmentioning
confidence: 92%
“…In a number of publications, we have shown that the substitution of heterocycles rich in nitrogen-like purines [1], indazoles [2], triazoles [3], oxadiazoles [4], imidazoles [5], pyrimidocinnolines [6], or phthalazines [7] with a carboxamide partial structure, a hydrophobic moiety and basic groups leads to a wide variety of compounds with antiplatelet activities in micromolar concentrations. In this paper, we wish to report a number of thiazole derivatives fulfilling these structural requirements and, consequently, were promising to show remarkable antiplatelet activities.…”
Section: Introductionmentioning
confidence: 99%